Bamboo‐Like Nanozyme Based on Nitrogen‐Doped Carbon Nanotubes Encapsulating Cobalt Nanoparticles for Wound Antibacterial Applications. (16th July 2021) - He, Shaoying; Huang, Junqin; Zhang, Qiang; Zhao, Wan; Xu, Zhiai; Zhang, Wen
Abstract: In this paper, an artificial nanozyme with efficient oxidase‐mimicking activity is developed to investigate antibacterial performance. The bamboo‐like nitrogen‐doped carbon nanotubes encapsulating cobalt nanoparticles (N‐CNTs@Co) are synthesized by pyrolysis of cobalt cyanide cobalt at high temperature. It is found that the oxidase‐mimicking activity of N‐CNTs@Co is higher than that of iron‐centered nanomaterials synthesized by pyrolysis of prussian blue under the same conditions, confirming that the oxidase‐mimicking activity is not only related to the active center, but also closely related to its morphology. In addition, the oxidase‐mimicking activity of N‐CNTs@Co is 12.1 times higher than that of the most reported CeO2 . N‐CNTs@Co can catalyze oxygen to produce a large number of reactive oxygen species (ROS) under acidic conditions, resulting in a favorable antibacterial effect against two representative bacteria, Gram‐positive ( Staphylococcus aureus ) and Gram‐negative ( Escherichia coli ). Because the bacterial membrane is damaged by the attack of ROS, the DNA is degraded, eventually causing the bacteria to die. Antibacterial experiments last for 20 days, nevertheless, S. aureus and E. coli do not develop resistance to N‐CNTs@Co. The experiments of wound healing in vivo further confirm the high antibacterial efficiency of N‐CNTs@Co. Abstract : The antibacterial application of N‐CNTs@Co is presented.